Emancipation and Legal Justice; Portrait of Women's Legal Protection In Indonesia - Kemala Dewi, Mentari Berliana; Arifin, Ridwan (Jurnal Cita Hukum, 2019)
Abstract. International human rights declarations urge the development of feminism in the world. Feminism whose essence is fighting for women's rights has so far been neglected by the community, so that a new spirit is sought so that women can again feel. This study aims to review unfairness actions that have been scattered in society between men and women. Justice is expressed in daily life in order to eradicate acts of gender discrimination. Indonesia as a legal state that always obeys the law and upholds the principles of justice and certainty is a reflection of an existing feminist movement. The role of women must be considered important by the progress of a nation, however in Indonesia there are still many issues of gender equality that occur, such as the absence of women's own beliefs in matters of occupying good power. The problem of sexual crimes that have been wiping out in all public relations has led to increasingly ineffective emancipation of women in Indonesia. This emancipation is a form or manifestation of the feminist movement that can benefit both men and women. The feminism movement can encourage relations in a harmonious society to maintain a stable condition. Keywords: Emancipation, Trust, Justice, Women, Crime Abstrak.Deklarasi HAM internasional mendesak perkembangan feminisme di dunia. Feminisme yang hakikatnya memperjuangkan hak-hak perempuan sejauh ini telah diabaikan oleh masyarakat, sehingga semangat baru dicari sehingga perempuan dapat kembali merasakan. Penelitian ini bertujuan untuk mengkaji tindakan tidak adil yang telah tersebar di masyarakat antara pria dan wanita. Keadilan diekspresikan dalam kehidupan sehari-hari untuk menghapus tindakan diskriminasi gender. Indonesia sebagai negara hukum yang selalu mematuhi hukum dan menjunjung tinggi prinsip keadilan dan kepastian adalah cerminan dari gerakan feminis yang ada. Peran perempuan harus dianggap penting oleh kemajuan suatu bangsa, namun di Indonesia masih banyak masalah kesetaraan gender yang terjadi, seperti tidak adanya keyakinan perempuan sendiri dalam hal menduduki kekuasaan yang baik. Masalah kejahatan seksual yang telah memusnahkan di semua hubungan masyarakat telah menyebabkan emansipasi perempuan yang semakin tidak efektif di Indonesia. Emansipasi ini adalah bentuk atau manifestasi dari gerakan feminis yang dapat bermanfaat baik bagi pria maupun wanita. Gerakan feminisme dapat mendorong hubungan dalam masyarakat yang harmonis untuk mempertahankan kondisi yang stabil.Kata Kunci: Emansipasi, Kepercayaan, Keadilan, Perempuan, Kejahatan Аннотация.Международные декларации прав человека призывают к развитию феминизма в мире. Феминизм, суть которого заключается в борьбе за права женщин, до сих пор игнорировался сообществом, так что ищется новый дух, чтобы женщины снова могли чувствовать. Это исследование направлено на рассмотрение действий несправедливости, которые были разбросаны в обществе между мужчинами и женщинами. Справедливость выражается в повседневной жизни с целью искоренения актов гендерной дискриминации. Индонезия как правовое государство, которое всегда подчиняется закону и придерживается принципов справедливости и определенности, является отражением существующего феминистского движения. Роль женщин должна рассматриваться как важная для прогресса нации, однако в Индонезии по-прежнему существует много проблем гендерного равенства, таких как отсутствие собственных убеждений женщин в вопросах занятия хорошей властью. Проблема сексуальных преступлений, которая исчезла во всех общественных отношениях, привела к все более неэффективной эмансипации женщин в Индонезии. Эта эмансипация является формой или проявлением феминистского движения, которое может принести пользу как мужчинам, так и женщинам. Движение феминизма может поощрять отношения в гармоничном обществе для поддержания стабильного состояния.Ключевые слова: эмансипация, доверие, справедливость, женщины, преступность